Reproductive health in the young cuban - Guerrero Borrego, Natividad (Última Década, 2020)
One of the most important decisions in the lives of people is to have children or not. The trend of Cuban couples is starting a family at some point in their lives. Cuba achieved the lowest levels of fertility in the Latin American scene, two decades ahead the rest of the region. The Center for Youth Studies has vast experience in dealing with sexual and reproductive health of young people. This report aims to contribute reflections taxing debate on sexual and reproductive health in the young Cuban.